One Hundred Years of Dirt - Morton, Rick (Melbourne University Press Digital, 2018)
Violence, treachery and cruelty run through the generational veins of Rick Morton's family. A horrific accident thrusts his mother and siblings into a world impossible for them to navigate, a life of poverty and drug addiction. One Hundred Years of Dirt is an unflinching memoir in which the mother is a hero who is never rewarded. It is a meditation on the anger, fear of others and an obsession with real and imagined borders. Yet it is also a testimony to the strength of familial love and endurance.